Epidemiology and etiology of infantile developmental and epileptic encephalopathies in Tasmania. Issue 3 (22nd July 2019) - Ware, Tyson L.; Huskins, Shannon R.; Grinton, Bronwyn E.; Liu, Yu‐Chi; Bennett, Mark F.; Harvey, Michael; McMahon, Jacinta; Andreopoulos‐Malikotsinas, Danae; Bahlo, Melanie; Howell, Katherine B.; Hildebrand, Michael S.; Damiano, John A.; et al.
Abstract: We sought to determine incidence, etiologies, and yield of genetic testing in infantile onset developmental and epileptic encephalopathies (DEEs) in a population isolate, with an intensive multistage approach. Infants born in Tasmania between 2011 and 2016, with seizure onset <2 years of age, epileptiform EEG, frequent seizures, and developmental impairment, were included. Following review of EEG databases, medical records, brain MRIs, and other investigations, clinical genetic testing was undertaken with subsequent research interrogation of whole exome sequencing (WES) in unsolved cases. The incidence of infantile DEEs was 0.44/1000 per year (95% confidence interval 0.25 to 0.71), with 16 cases ascertained. The etiology was structural in 5/16 cases. A genetic basis was identified in 6 of the remaining 11 cases (3 gene panel, 3 WES). In two further cases, WES identified novel variants with strong in silico data; however, paternal DNA was not available to support pathogenicity. The etiology was not determined in 3/16 (19%) cases, with a candidate gene identified in one of these. Pursuing clinical imaging and genetic testing followed by WES at an intensive research level can give a high diagnostic yield in the infantile DEEs, providing a solid base for prognostic and genetic counseling.